2017
DOI: 10.1016/j.jelekin.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and criterion validity of 2D video assessment of single leg squat and hop landing

Abstract: The objective was to assess the intra-tester, within and between day reliability of measurement of hip adduction (HADD) and frontal plane projection angles (FPPA) during single leg squat (SLS) and single leg landing (SLL) using 2D video and the validity of these measurements against those found during 3D motion capture. 15 healthy subjects had their SLS and SLL assessed using 3D motion capture and video analysis. Inter-tester reliability for both SLS and SLL when measuring FPPA and HADD show excellent correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 9 publications
4
44
0
2
Order By: Relevance
“…1, was chosen for risk factor analysis. The FPA measured in a similar, but not identical 2D single-leg landing task has shown good correlation with 3D measurements [31]. Using the same methods as this study, Stensrud et al observed moderate to excellent reliability when they measured lower extremity kinematics during the SLVDJ (ICC range = 0.58-0.89) [26].…”
Section: Study Design and Data Collectionsupporting
confidence: 61%
“…1, was chosen for risk factor analysis. The FPA measured in a similar, but not identical 2D single-leg landing task has shown good correlation with 3D measurements [31]. Using the same methods as this study, Stensrud et al observed moderate to excellent reliability when they measured lower extremity kinematics during the SLVDJ (ICC range = 0.58-0.89) [26].…”
Section: Study Design and Data Collectionsupporting
confidence: 61%
“…Firstly, kinematic data were collected using 2D video footage, which in comparison to "gold standard" 3D motion capture, does not account for movement in all planes of motion and segmental and joint rotations. However, research has shown acceptable agreement between 2D and 3D analysis methods 33,34 , and many of the injury risk factors associated with the knee occur in the sagittal and frontal planes. Additionally, due to financial costs and time-consuming nature of testing, many 3D motion capture systems are impractical for applied settings, especially when attempting to screen large groups of young players in the setting of a soccer academy.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst 3D motion capture is a useful tool for elite sports performance and research the time required for data capture and processing makes it difficult to provide immediate clinical information [4].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of processed 2D video images has shown good intra-rater reliability (Intra-class correlation coefficients (ICC) > 0.59) [17], inter-rater reliability (ICC > 0.96) and validity (r = 0.81) when assessing knee valgus and hip adduction angles [4]. Annotation of still video pictures whilst more practical than 3D motion capture is still removed from immediate dynamic assessment in vivo.…”
Section: Introductionmentioning
confidence: 99%